ChemInform Abstract: Brook Rearrangement as a Trigger for the Ring Opening of Strained Carbocycles. Issue 21 (6th May 2016) - Zhang, Fa‐Guang; Eppe, Guillaume; Marek, Ilan
Abstract: The diastereoselective copper‐catalyzed carbomagnesiation of cyclopropenyl amides (I) followed by reaction with acylsilanes gives functionalized hydrosilanes (IV) with high diastereoselectivity.